Analisis Motivasi Karir, Pengembangan Kompetensi, dan Penghargaan Finansial Terhadap Persepsi Minat Sertifikasi profesi Akuntansi (Studi Kasus Mahasiswa Akuntansi UPN “Veteran” Jawa Timur) - Ubbadullah, Ubbadullah; Budiwitjatsono, Gideon Setyo (Ekonomis: Journal of Economics and Business, 2024)
This study aims to examine and prove the effect of career motivation, competency development, andfinancial rewards on the perception of interest in accounting profession certification at UPN "Veteran" East Java. This study uses a quantitative approach. The population as well as the sample in this study were all accounting students at UPN "Veteran" East Java class of 2019-2022, namely 1190 and the number of samples used was 92 respondents. The type of data used in this study is primary data derived from respondents' answers obtained from filling out questionnaires that have been distributed to all accounting students at UPN "Veteran" East Java. The data analysis techniqueused in this study uses Partial Least Square (PLS). The results of the study show that Competency Development has no effect on Interest in Accounting Professional Certification. While Career Motivation and Financial Rewards have an effect on Interest in Accounting Professional Certification.